Purtscher's retinopathy after fracture dislocation of shoulder joint. Issue 11 (21st October 2005) - Nayak, H; Harun, S; Palimar, P
Abstract : Purtscher described sudden blindness in patients with severe head trauma due to a remote retinopathy, characterised by bilateral retinal haemorrhages, cotton wool spots, and optic disc swelling seen on fundoscopy. A similar retinopathy has been reported in compressive chest trauma, long bone fractures, and acute pancreatitis. It is less well recognised that Purstcher's retinopathy can occur unilaterally and following less severe trauma. We present a case of unilateral remote traumatic retinal angiopathy following a fracture dislocation of the shoulder joint.